2020
DOI: 10.1021/acs.iecr.9b04561
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Filtering and Residual Analysis in Errors-in-Variables Model Identification

Abstract: Dynamic model identification from time series data is a critical component of process control, monitoring, and diagnosis. An important adjunct of model identification is the derivation of filtered estimates of the variables and consequent one-step-ahead prediction errors (residuals) which are very useful for model assessment and iterative model identification. In this work, we present an optimal filtering and residual generation method for the errors-in-variables (EIV) scenario, wherein both the input and outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…From Table IV, It can be clearly observed that the last 5 eigenvalues are not equal to unity for d guess = 5, while for d guess = 4, it can be observed that the last 4 eigenvalues are approximately unity. This can also be confirmed from hypothesis testing for equality of the smallest d guess eigenvalues, which are expected to be unity [28]. The results for hypothesis testing for each value of d guess are reported in Table V.…”
Section: A Example 1: Siso Second Order Systemsupporting
confidence: 63%
See 2 more Smart Citations
“…From Table IV, It can be clearly observed that the last 5 eigenvalues are not equal to unity for d guess = 5, while for d guess = 4, it can be observed that the last 4 eigenvalues are approximately unity. This can also be confirmed from hypothesis testing for equality of the smallest d guess eigenvalues, which are expected to be unity [28]. The results for hypothesis testing for each value of d guess are reported in Table V.…”
Section: A Example 1: Siso Second Order Systemsupporting
confidence: 63%
“…The lagged data matrix Z L is constructed for L = 6, and the proposed algorithm is applied starting with the maximum possible value of d guess = 6. We apply the hypothesis test as described in [28] to test whether the smallest d guess eigenvalues are all equal. The hypothesis test results are presented in Table X for different values of d guess .…”
Section: B Example 2: Siso With System Order 3 and Input Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four free model parameters in (62) were regressed by minimum least-squares using a global optimization algorithm. We choose a global over a local solver given our model's strong nonlinearities and multiple free parameters, making it prone to falling into a local optimum.…”
Section: Resultsmentioning
confidence: 99%
“…States are represented by (59), implicit variables by (60), and input variables by (61), which include the manipulated variables and measured disturbance 𝑇 𝑤.𝑖𝑛 . The four model parameters in (62) were regressed from the experimental data. A consistent initial condition is obtained by solving ( 55) and ( 56) simultaneously at steady-state (zeros on the left-hand side).…”
Section: ) Numerical Solution and Simulationmentioning
confidence: 99%